THE IMPLEMENTATION OF MULTIPATH RAYLEIGH FADING CHANNEL USING INFINITE IMPULSE RESPONSE (IIR) FILTER IN TMS320C6713 DSK - HANA LESTARI (NIM : 13206014); Pembimbing : Dr. Effrina Yanti Hamid, ST, MT, FADHILAH
In wireless communication systems, the phenomenon of multipath fading is unavoidable. In order to know the performance of this communication system, a software or hardware prototype of multipath fading channel is needed to approach the actual channel condition. In this final project, the author is interested in developing a hardware prototype of multipath fading channel using TMS320C6713 DSK. The first thing to do is to design the Rayleigh fading signal generation. The method used involves an IIR filter and an interpolator. Then, it is simulated by using MATLAB, a simulation in C language using CCS, which is then implemented into TMS320C6713 DSK The implementation is divided into a real-time and a non real-time. The realtime implementation uses a signal generator as input signals and the non real-time implementation uses BPSK and OFDM communication system in its processing signal. From the test, the author found that the pdf histogram of Rayleigh fading signal has a distribution that approximates the theoretical values. From the calculation of channel parameters, the fading signals have the characteristics of slow fading and frequency-selective fading.